Analysis of Factors Influencing The Incidence of DangueHemorrhagic Fever (DBD) In Semarang City - Basuki, Yunita Rohmawati; Indriyanti, Dyah Rini; Wijayanti, Yuni (Public Health Perspective Journal, 2024)
Dengue Hemorrhagic Fever is an infectious disease caused by acute viral infection, namely the dengue virus. Symptoms include fever for 2-7 days, accompanied by signs of bleeding, a decrease in the number of platelets (thrombocytopenia), and plasma leakage characterized by hemoconcentration. The aim of this study is to analyze the factors that most influence the incidence of dengue fever in the city of Semarang. This research uses a case control research design. The case population is all dengue sufferers, while the control population is people who are declared negative for dengue fever through microscopic examination of blood smears. The sample consisted of 2 groups, namely 45 respondents in the case group and 45 respondents in the control group, accompanied by the use of purposive random sampling techniques. The instrument uses a questionnaire sheet. Data analysis used the Chi Square test and Logistic Regression test. The results of the research show that there is a correlation between water storage, level of knowledge, efforts to eradicate mosquito nesting areas, use of anti-mosquito medication and behavior of hanging clothes with dengue cases (p-value < 0.05). Factors that influence the incidence of dengue fever are water storage, level of knowledge, and efforts to eradicate mosquito nests. It is necessary to carry out preventive efforts independently for each family member.